PPARα Gene Is Involved in Body Composition Variation in Response to an Aerobic Training Program in Overweight/Obese - Glêbia A. Cardoso; Mateus D. Ribeiro; Bruno R. V. Sousa; Yohanna de Oliveira; Klécia F. Sena; Joane R. E. Batista; Antônio E. M. Almeida; João M. Filho; Raquel S. B. Silva; Darlene C. Persuhn; Alexandre S. Silva (PPAR Research)
The objective of this study was to investigate the relationship of the polymorphism in Intron 7 G/C (rs 4253778) of the peroxisome proliferator-activated receptor alpha (PPARα) gene with the magnitude of changes in the body composition of an overweight and obese population that underwent an aerobic training program. Fifty-eight previously inactive men and women, body mass index (BMI) 31.5±2.8 kg/m2, 46.5% (n=27) genotyped as CC genotype and 53.5% (n=31) as CA+AA, underwent a 12-week aerobic training (walking/running). Aerobic capacity (ergospirometry), body composition (DXA), and nutritional assessment were made before and 48 h after the experimental protocol. Two-way ANOVA, chi-square test, and logistic regression were used (p<0.05). Twenty-seven volunteers (46.5%) were identified as CC genotype and 31 (53.5%) as CA+AA genotype. Time-group interaction showed that there was no difference in these between two allele groups. However, differences in distribution of respondents or nonresponders according to allele A were identified for fat mass (p≤0.003), percentage fat mass (p≤0.002), the waist (p≤0.009), abdomen (p≤0.000), and hip (p≤0.001), this difference being independent for the fat mass. Meanwhile, sex, age, and nutritional management have also been found to be influential factors. It is concluded that the PPARα gene is involved in varying body composition in response to an aerobic training program.